2014
DOI: 10.1016/j.pt.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The proliferating cell hypothesis: a metabolic framework for Plasmodium growth and development

Abstract: HighlightsThe hypothesis offers a framework to explain the atypical features of parasite metabolism.Aerobic glycolysis is hypothesised to meet the biosynthetic demands of rapid proliferation.Differentiation may be epigenetically regulated in response to nutrient-linked metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 50 publications
4
49
0
Order By: Relevance
“…This is in line with previous studies [44] and pointed towards the rapid turnover of glycolytic end products in iRBC to downstream metabolites via the TCA cycle and/or intermediary carbon metabolism or for rapid biomass generation to help in proliferative schizogony [45]. Although pre-existing pools of glucose in the host cell can contribute to glycolysis in the parasite, the direct role of the host cell glycolytic pathway in development of intracellular parasites is unclear as the parasite glycolytic machinery is well established [46] and is supported by increased internalisation of glucose into the infected cell owing to expression of glucose transporters on the surface of the infected cell [32].…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous studies [44] and pointed towards the rapid turnover of glycolytic end products in iRBC to downstream metabolites via the TCA cycle and/or intermediary carbon metabolism or for rapid biomass generation to help in proliferative schizogony [45]. Although pre-existing pools of glucose in the host cell can contribute to glycolysis in the parasite, the direct role of the host cell glycolytic pathway in development of intracellular parasites is unclear as the parasite glycolytic machinery is well established [46] and is supported by increased internalisation of glucose into the infected cell owing to expression of glucose transporters on the surface of the infected cell [32].…”
Section: Discussionsupporting
confidence: 92%
“…In support of this observation, studies in Schistosoma japonicum-infected mice exposed to artemether also showed an effect of drug treatment on important glycolytic enzymes in the parasite (39,40). In general, these findings are consistent with the vital and essential role that glycolytic enzymes play in supporting rapid growth and proliferation, similar to that seen in other rapidly proliferating cells, such as cancer cells (41,42). The high glycolytic flux of intraerythrocytic developmental cycle maintains rate-limiting glycolytic intermediates to support other pathways (e.g., nucleotide and lipid biosynthesis) (Fig.…”
Section: Resultssupporting
confidence: 85%
“…In a manner analogous to the Warburg effect observed in highly-proliferative cancer lines and other rapidly-growing cells (e.g., yeast and bloodstream Trypanosoma spp. ), Plasmodium (in erythrocytic stages) has opted for fast generation of ATP through substrate-level phosphorylation and secretion of lactate as an end-product (aerobic fermentative glycolysis), as opposed to the 'slow but efficient' mitochondrial oxidative phosphorylation and complete oxidation [29]. Reasons for this dependence on glycolytic fermentation remain unclear -after all, blood stages of Plasmodium certainly have access to oxygen -but it may be a way of avoiding excessive reactive oxygen species (ROS) production in an environment already under considerable stress due to hemoglobin breakdown [30,31].…”
mentioning
confidence: 99%